Maternal circulating osteoprotegerin and soluble RANKL in pre-eclamptic women - Vitoratos, N.; Lambrinoudaki, I.; Rizos, D.; Armeni, E.; Alexandrou, A; Creatsas, G. (European Journal of Obstetrics Gynecology and Reproductive Biology, 2011)
Objective: To evaluate alterations in the concentrations of osteoprotegerin (OPG), RANKL and the OPG/RANKL ratio in pre-eclamptic women during the puerperium. Study design: This cross-sectional study was performed in the maternity ward of Aretaieio Hospital in Athens, Greece. Fifteen pregnant women with severe pre-eclampsia and 15 matched controls with premature rupture of the membranes were recruited. Fasting blood samples were obtained antepartum, immediately after diagnosing pre-eclampsia (median: 32nd gestational week), and during the 3rd-6th day postpartum, to estimate levels of circulating OPG and RANKL as well as the OPG/RANKL ratio. The anthropometric parameters evaluated included body mass index and blood pressure. Results: Mean circulating OPG levels decreased significantly in both groups in the postpartum period (controls: 43.7 ± 19.1 ng/ml vs 22.9 ± 9.1 ng/ml, p = 0.008; pre-eclamptic group: 72.3 ± 49.9 vs 49.7 ± 40.9 ng/ml, p = 0.002). The antepartum OPG/RANKL ratio was elevated in hypertensive pregnancies (2.41 ± 1.72) compared to normotensive pregnancies (1.45 ± 0.63), but the difference did not reach statistical significance (p = 0.1). The OPG/RANKL ratio decreased in the control group (0.76 ± 0.30, NS) following delivery, while it remained unchanged in the pre-eclamptic women (1.63 ± 1.40, p = 0.13). Consequently, the postpartum OPG/RANKL ratio was significantly higher in the pre-eclamptic women compared to control women (1.63 ± 1.40 vs 0.76 ± 0.30, p = 0.01). Levels of RANKL demonstrated no significant alterations during puerperium in both cases. Conclusion: Pregnancies complicated with pre-eclampsia exhibit higher OPG levels and OPG/RANKL ratios, compared to control pregnancies, which might be compatible with lower bone turnover. The significance of this finding with respect to bone metabolism remains to be elucidated in larger studies. © 2010 Elsevier Ireland Ltd.
Keywords: Bone turnover; Osteoprotegerin; Pre-eclampsia; RANKL